Lower platelet count with increased density of platelet antigens in granulocyte colony-stimulating factor mobilized peripheral blood stem cell donors - Yi-feng Wu; Ming-huei Gu; Shang-hsien Yang; Tso-fu Wang (Journal of the Formosan Medical Association, 2020)
Background/purpose: Granulocyte colony-stimulating factor (G-CSF) is widely used for prophylaxis and treatment of neutropenia in cancer patients and also for peripheral blood stem cells (PBSC) mobilization. The aim of this study is to evaluate the possible changes of platelet surface antigens after G-CSF injection in PBSC donors compared with healthy control. Methods: Between January 1st and December 31st, 2014, 48 healthy voluntary PBSC donors were eligible for this study. Donors received G-CSF (Filgrastim) subcutaneously for five days, and then their whole blood was collected for complete blood count. Analysis of platelet antigens was performed by flow cytometry. Sixteen healthy controls were also included for comparison. Results: Lower platelet counts were found in PBSC donors after G-CSF use and in comparison with health controls. The platelet size evaluated by forward scattering (FSC) showed smaller platelets in PBSC donors after G-CSF use compared with healthy controls (39.3 vs 46.7 mean fluorescence intensity, P = 0.015). CD31 were higher in PBSC donor (203.2 vs. 120.7, P < 0.001). Except CD31, other platelet surface antigens were not different between PBSC donors and healthy controls. After adjusting by FSC data, the mean antigen intensity/FSC of CD31, CD41a, CD42a, CD42b and CD61 showed 5.45 vs 2.78 (P < 0.001), 4.35 vs 3.47 (P = 0.007), 3.87 vs 3.17 (P = 0.015), 20.45 vs 16.94 (P = 0.045), and 5.98 vs 4.88 (P = 0.018) respectively. Conclusion: We noted higher density of platelet surface antigens, lower platelet count and smaller platelet size after G-CSF injection. Keywords: G-CSF, Platelet, Flow cytometry, Immunophenotyping, Hematopoietic stem cell mobilization